Archaeal Life on Tangkuban Perahu- Sampling and Culture Growth in Indonesian Laboratories - SRI HANDAYANI; IMAN SANTOSO; HANS-JOACHIM FREISLEBEN; HARALD HUBER; . ANDI; FERY ARDIANSYAH; CENMI MULYANTO; ZESSINDA LUTHFA; ROSARI SALEH; SERUNI KUSUMA UDYANINGSIH FREISLEBEN; SEPTELIA INAWATI WANANDI; MICHAEL THOMM (Bogor Agricultural University, Indonesia, 2012)
The aim of the expedition to Tangkuban Perahu, West Java was to obtain archaeal samples from the solfatara fields located in Domas crater. This was one of the places, where scientists from the University of Regensburg Germany had formerly isolated Indonesian archaea, especially Thermoplasma and Sulfolobus species but not fully characterized. We collected five samples from mud holes with temperatures from 57 to 88 oC and pH of 1.5-2. A portion of each sample was grown at the University of Regensburg in modified Allen’s medium at 80 oC. From four out of five samples enrichment cultures were obtained, autotrophically on elemental sulphur and heterotrophically on sulfur and yeast extract; electron micrographs are presented. In the laboratories of Universitas Indonesia the isolates were cultured at 55-60 oC in order to grow tetraetherlipid synthesizing archaea, both Thermoplasmatales and Sulfolobales. Here, we succeeded to culture the same type of archaeal cells, which had been cultured in Regensburg, probably a Sulfolobus species and in Freundt’s medium, Thermoplasma species. The harvested cells are documented by phase contrast microscope equipped with a digital camera. Our next steps will be to further characterize genetically the cultured cells from Tangkuban Perahu isolates.